2007
DOI: 10.1063/1.2709617
|View full text |Cite
|
Sign up to set email alerts
|

Structural phase transitions of Ge2Sb2Te5 cells with TiN electrodes using a homemade W heater tip

Abstract: The phase transitions of a Ge2Sb2Te5 cell with a volume of 20×20×0.1μm3 were carried out by applying a reset pulse (10V and 50ns) and a subsequent set pulse (5V and 300ns) using a homemade W heater tip fabricated by focused ion beam lithography. The phase transformation from a crystalline state to an amorphous state was confirmed by measuring the I-V curves and observation with a cross-sectional transmission electron microscope both before and after applying the reset pulse. The electron diffraction pattern ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 19 publications
1
17
0
Order By: Relevance
“…Among these attempts is the investigation on scanning probe based storage systems where, similarly to the PCRAM cells, writing of bits by conductive probes involves an electrothermal process in which Joule heating provides the energy required for film crystallization or amorphization. [9][10][11][12][13][14] In this work we report that microstructural and conductivity change of crystalline Ge 2 Sb 2 Te 5 films in the nanoscale range can also be obtained by a mechanical process via nanoscratching. In analogy with laser or electrical writing, the mechanically modified film regions have much lower conductivity than unmodified regions and show microstructural features that are consistent with the amorphous state of the Ge 2 Sb 2 Te 5 alloy.…”
mentioning
confidence: 79%
“…Among these attempts is the investigation on scanning probe based storage systems where, similarly to the PCRAM cells, writing of bits by conductive probes involves an electrothermal process in which Joule heating provides the energy required for film crystallization or amorphization. [9][10][11][12][13][14] In this work we report that microstructural and conductivity change of crystalline Ge 2 Sb 2 Te 5 films in the nanoscale range can also be obtained by a mechanical process via nanoscratching. In analogy with laser or electrical writing, the mechanically modified film regions have much lower conductivity than unmodified regions and show microstructural features that are consistent with the amorphous state of the Ge 2 Sb 2 Te 5 alloy.…”
mentioning
confidence: 79%
“…A Pt C-AFM probe with a 5 nm radius is used to make electrical contact with the TiN top electrode, and trapezoidal RESET and SET voltage pulses of various amplitudes (1 -2 V) and durations (40-100 ns) are applied to the top of the C-AFM probe, whilst the boundary of the Si substrate is maintained at ground potential (as shown previously in [5,7]). To avoid interference between neighboring cells, the top TiN electrode is patterned to cover the GST layer only (as proposed in [18]). …”
Section: B Simulations Of Pp-pcm Cell Structurementioning
confidence: 99%
“…The choice of capping layer is crucial as it not only protects the active phase-change region from oxidation and wear, but also provides a conductive path for the current required for electrical switching, and consequently has a strong influence on the resulting temperature distributions inside the active region [5,7]. TiN is a well-known electrode material and has previously been used in GST-based patterned PCM cells to demonstrate electrical switching [18,19]. Amorphous to crystalline phase transitions in GST films as thin as 2 nm have also been reported in [2] using a trilayer TiN/GST/TiN structure.…”
Section: A Choice Of Pp-pcm Cell Structurementioning
confidence: 99%
See 1 more Smart Citation
“…10 where a 20 nm diameter cylinder of GST is embedded in an SiO 2 matrix. Extended to a checkerboard type pattern, such a geometry would yield a storage density approaching 1 Tbit/sq.in.. Kim et al [39] have already demonstrated experimentally the ability to induce switching in patterned GST media, both from the crystalline state to the amorphous state and back again. However, they used patterning on the micrometer scale and a very large (18 m) tungsten tip.…”
Section: A Patterned Mediamentioning
confidence: 99%